Terapi Hipnosis dalam Menurunkan Kecemasan Mahasiswa Magister Ilmu Keperawatan - Dwi Sartika; Eni Marwanti; Ifana Yunike Pristya; Riska Eka Fatma Hasibuan (Malahayati Nursing Journal, 2025)
ABSTRACT Anxiety is the largest mental disorder in the world. It can occur in anyone, including master of nursing students. These students undertake their education over four semesters. They face not only academic burdens, such as assignments, but also work-related burdens for those studying with study permits, as well as financial costs and study completion targets. The study aims to investigate the effect of hypnotherapy on reducing anxiety among master of nursing students. This research is a pre-experimental study with a time-series approach on a single intervention group with three measurements: before, immediately after, and one week after the hypnotherapy intervention. The population of this study is master of nursing students, with a sample size of 15 respondents selected through convenience sampling. The repeated measures anova test resulted in p-value of 0.001, indicating significant differences in anxiety levels at the three measurements point. Bivariate analysis revealed no significant associations between anxiety and confounding factors such as age, social support, gender, marital status, living status, study status, and study funding. Hypnotherapy can reduce anxiety among master of nursing students and can be an effective non-pharmacological therapy to reduce anxiety of master’s nursing students. Keywords: Hypnotherapy, Anxiety, Master of Nursing Student  ABSTRAK Kecemasan merupakan gangguan mental terbesar di dunia. Kecemasan dapat terjadi pada siapa saja tidak terkecuali mahasiswa magister ilmu keperawatan. Mahasiswa magister ilmu keperawatan menempuh pendidikan selama 4 semester. Mereka tidak hanya memiliki beban akademik yang meliputi tugas akademik, namun juga beban pekerjaan bagi mahasiswa yang kuliah dengan ijin belajar, serta biaya dan target penyelesaian masa studi. Penelitian ini bertujuan untuk mengetahui pengaruh terapi hipnosis dalam menurunkan kecemasan mahasiswa magister ilmu keperawatan. Penelitian ini menggunakan desain pre-eksperimen dengan pendekatan time series pada 1 kelompok intervensi dengan tiga kali pengukuran yaitu sebelum, sesaat setelah dan satu minggu setelah diberikan intervensi terapi hipnosis. Populasi penelitian ini yaitu mahasiswa magister ilmu keperawatan dengan jumlah sampel yaitu 15 responden dengan teknik pengambilan sampel yaitu convenience sampling. Uji anova repeated measures didapatkan nilai p0,001 sehingga disimpulkan terdapat perbedaan yang bermakna kecemasan pada ketiga pengukuran. Hasil analisa bivariat didapatkan tidak terdapat hubungan yang bermakna antara kecemasan dengan umur, dukungan sosial, jenis kelamin, status pernikahan, status tinggal, status belajar dan pembiayaan kuliah. Terapi hipnosis dapat menurunkan kecemasan mahasiswa magister ilmu keperawatan sehingga dapat digunakan sebagai terapi nonfarmakologis dalam menurunkan kecemasan mahasiswa magister ilmu keperawatan. Kata Kunci: Terapi Hipnosis, Kecemasan, Mahasiswa Magister Ilmu Keperawatan